Accuracy of water vapor permeability of building materials reassessed by measuring cup's inner relative humidity. (1st June 2022) - Colinart, T.; Glouannec, P.
Abstract: Cup experiments are the most widely used method to measure the water vapor permeability of porous building materials. For this test, cup assembly is designed to create a vapor pressure gradient across a sample and, thus, to allow vapor diffusion through it. Water vapor permeability is assessed by weighing cup assembly over time. While the external conditions are generally well controlled, appropriate solid desiccants or saturated salt solutions are used to control the conditions inside the cup. However, precise knowledge of these conditions is crucial, as they are used to calculate permeance and hence water vapor permeability. In this study, dry and wet cup experiments were performed with different solid desiccants or saturated salt solutions on nine materials with Sd-values ranging from 0.08 m to more than 1 m. In all the experiments, the relative humidity within the air layer in the cup was measured with wireless sensors. The results showed that relative humidity was rarely the same as the expected value and that the relative humidity of solid desiccant also varied over time, resulting in from 5% to 450% relative errors in the predicted Sd-value. A correction method is proposed to assess the "real" Sd-value from the theoretical Sd-value and differences between dry and wet cup experiments are discussed. Highlights: Dry and wet cup experiments on nine materials with different permeability. Tests performed with solid desiccants or saturated salt solutions. Relative humidity measured within the air layer in the cup with a wireless sensor. Measured RH differed from the expected value and may also vary over time. Relative errors in the predicted Sd-value ranged between 5% and 450%.